Entrepreneurial finance, credit cards, and race - Chatterji, Aaron K.; Seamans, Robert C. (Journal of Financial Economics, 2012)
This paper examines the impact of financial deregulation on entrepreneurship. We assess the impact of credit card deregulation on transitions into self-employment using state-level removal of credit card interest rate ceilings following the US Supreme Court's 1978 Marquette decision as a quasi-natural experiment. We find that credit card deregulation increases the probability of entrepreneurial entry, with a particularly strong effect for black entrepreneurs. We demonstrate that these effects are magnified in states with a history of racial discrimination and link the results to discrimination-based barriers to entry.